DNA replication stress and cancer chemotherapy. Issue 2 (22nd December 2017) - Kitao, Hiroyuki; Iimori, Makoto; Kataoka, Yuki; Wakasa, Takeshi; Tokunaga, Eriko; Saeki, Hiroshi; Oki, Eiji; Maehara, Yoshihiko
Abstract : DNA replication is one of the fundamental biological processes in which dysregulation can cause genome instability. This instability is one of the hallmarks of cancer and confers genetic diversity during tumorigenesis. Numerous experimental and clinical studies have indicated that most tumors have experienced and overcome the stresses caused by the perturbation of DNA replication, which is also referred to as DNA replication stress (DRS). When we consider therapeutic approaches for tumors, it is important to exploit the differences in DRS between tumor and normal cells. In this review, we introduce the current understanding of DRS in tumors and discuss the underlying mechanism of cancer therapy from the aspect of DRS. Abstract : This review summarizes how DNA replication stress is induced and determines the cell destiny in the process of tumor development. This review also explains how cancer therapeutic drugs exploit the stress in malignant tumors.